The Classcraft Utilization in Increasing Students’ Motivation in Learning English of Eleventh Grade at Senior High School - Lestari, Sriwindry; Baka, Charlie; Sampelolo, Rigel (Indonesian TESOL Journal, 2024)
This study aims to determine how significant the Calsscraft use to increase students’ motivation in learning English of eleventh grade at SMAN 3 Tana Toraja both the times when they were taught by it and the times they weren’t. Classcraft is a game-based learning platform that can increase students’ motivation, cooperation, and soft skills in and out of the classroom. This study focuses on the students’ motivation in learning English by taught using Class craft. Based on the result above, the researcher found that there were difficulties faced in English learning at SMAN 3 Tana Toraja, as one of the secondary education institutions in the Mengkendek area. One of the factors that causes these difficulties is the lack of motivation to learn English, which is the desire, interest, and goals that encourage students to learn English actively and continuously (Yuzulia, 2012). Motivation is one of the most significant things in the learning process. Without motivation, the purpose of learning is tough to achieve. When learners have it in their learning process, they will better understand the materials, especially English (Borah, 2021).The researcher used true experimental and quantitative methods to explore the objective the research. To collect the data the researcher used several steps: giving the pre-test for the students, giving treatment and then giving post-test for students, identifying and classifying the students’ motivation level. The findings showed that before treatment, most of the students got moderate level of motivation in learning English, and after treatment, most of the students got high level of motivation in learning english. Keywords: COVID-19; Motivation; Pandemic, Students.